Viruses and bacteria - Cyber Ed Inc. (Chico, Calif. : Cyber Ed, 1997)
Includes diagrams and animations, along with electron photomicrographs and narratives. Virus topics include : size, shapes and structures and attachment to host cell. Types of bacteria : archaebacteria, eubacteria, bacterial diseases and more.
System requirements : IBM-Compatible PC, 4 MB RAM, hard disk space 256k, Windows 3.1, 95 0r higher, Microsoft NT versions, S-VGA graphics, CD-ROM crive ( b2x speed prefered )
Keywords: Viruses; Bacteria